Does the firm size affect the profitability? Evidence from listed manufacturing companies in sri lanka - Kobika, R. (University of Jaffna, 2019)
The purpose of this study is to explore the effects of firm size on profitability of quoted manufacturing firms in Sri Lanka. In this study, data of 25 companies which were active in Colombo Stock Exchange (CSE) between the years 2013 to 2017 has been used. As indicators of firm profitability Return on Assets, Return on Equity and Net Profit Margin have been used whereas Total Assets and Total Sales have been utilized as indicators of firm size. Correlation and regression methods have been used in the empirical analysis. There is relationship between firm size and profitability of listed manufacturing firms, the findings reveal. In addition, the results showed that firm size has impact on profitability of the listed manufacturing firms in Sri Lanka.
Keywords: Firm size; Profitability; Manufacturing firms